Characterization and Evolutionary Analysis of a Novel H3N2 Influenza A Virus Glycosylation Motif in Southern China - Zeng, Zhiqi; Yau, Lee-Fong; Lin, Zengxian; Xia, Xuanzi; Yang, Zifeng; Wang, Jing-Rong; Song, Wenjun; Wang, Xinhua (Frontiers in Microbiology, 2020)
An influenza A (H3N2) virus epidemic occurred in China in 2017 and the causative strain failed to bind red blood cells (RBCs), which may affect receptor binding and antibody recognition. The objective of this study was to analyze the genetic characteristics and glycosylation changes of this novel H3N2 strain. We directly sequenced the hemagglutinin (HA) genes of H3N2 clinical specimens collected from patients with acute respiratory tract infection during 2017 in Guangdong, China. We aligned these sequences with those of A/Hong Kong/1/1968 (H3N2) and A/Brisbane/10/2007(H3N2). Glycosylation changes were analyzed by C18 Chip-Q-TOF-MS. A/China/LZP/2017(H3N2) was negative by HA assay, but was positive by quantitative real-time PCR and direct immunofluorescence assay. We found that the HA1 residue 160T of A/China/LZP/2017(H3N2) could block virus binding to receptors on RBCs. Furthermore, the N-X-T motif at HA1 residues 158–160, encoding a glycosylation site as shown by C18 Chip-Q-TOF-MS, predominated worldwide and plays a critical role in RBC receptor binding. Ten glycoforms at HA1 residue 158 were identified (4_3_1_0, 5_6_0_1, 3_3_0_1, 4_4_3_0, 6_7_0_0 (SO3), 3_6_2_0, 4_3_1_2 (SO3), 7_5_2_0 (SO3), 3_6_2_1 (SO3), and 3_7_0_2). Glycosylation changes at HA1 residues 158–160 of a circulating influenza A (H3N2) virus in Guangdong, China, in 2017 blocked binding to RBC receptors. Changes to these HA1 residues may have reduced protective antibody responses as well. Understanding these critical epitopes is important for selecting vaccine strains.